Comparative efficiencies of the decolourisation of Methylene Blue using Fenton’s and photo-Fenton’s reactions - Melgoza, D.; Hernández Ramírez, Aracely; Peralta Hernández, Juan Manuel (Royal Society of Chemistry, 2009)
The decolourisation and mineralization of Methylene Blue azo dye (MB) under Fenton’s and photo-Fenton’s conditions have been studied. Some parameters, such as initial concentrations of iron (Fe2+) and fixed hydrogen peroxide (H2O2), were evaluated to find the optimal conditions for the efficient degradation of azo dye. The experimental assays showed better efficiency for the photo-Fenton’s system. Pseudo-first order degradation rate constants were obtained from batch experimental set up. It is suggested that photo-Fenton’s reactions are viable processes for treatment of azo dye MB, according to the high levels of colour (UV665) and total organic carbon (TOC) removal.